When the Mirage Fades: Black Boys Encountering Antiblackness in a Predominantly White Catholic High School. Issue 7 (10th November 2022) - Thomas, Daniel J.; Johnson, Marcus W.; Clark, Langston; Harrison, Louis
ABSTRACT: Private high schools are often viewed as bastions of scholastic and social opportunities, but the cost of tuition has rendered these sites predominantly white and more segregated than public schools. However, with the ability to recruit, Black boys have become prime targets of predominantly white private Catholic high schools seeking promising student-athletes. As a result, the population of Black boys at these schools are composed almost entirely of students recruited to play a sport. Drawing from qualitative interview data, the purpose of this paper is to illustrate the racialized experiences of six Black boys who attended a predominantly white Catholic high school in which the entire Black population was composed of student-athletes. Findings indicate that participants initially saw the private Catholic school as an escape from their respective public schools but realized that mere attendance did not result in total inclusion. All six participants encountered forms of antiblackness via frequent structural and cultural assaults that made their daily attendance at the school difficult.